2018
DOI: 10.1080/16583655.2018.1507418
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring airborne pollution: a case study of “Urginea maritima” species in Bentael natural reserve – Lebanon

Abstract: Biomonitoring airborne pollution has been a widespread practice. Its advantages make it an alternative to costly technological techniques. In this context, a rare species "Urginea maritima" was tested to measure the changes surrounding Bentael natural reserve in Lebanon, triggered by the inauguration of a new road on its south side, and revealed alarming results through two years study (2015-2016). Three environmental indicators were evaluated: Air Pollution Tolerance Index, Total Antioxidant Capacity and leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…These results indicate that oxidative stress mainly occurred in the contaminated sites. The findings of this study were consistent with those of Khairallah et al (2018). They reported a remarkable increase of H 2 O 2 levels in roadside Urginea maritima leaves when compared with those growing at the control site.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 91%
See 2 more Smart Citations
“…These results indicate that oxidative stress mainly occurred in the contaminated sites. The findings of this study were consistent with those of Khairallah et al (2018). They reported a remarkable increase of H 2 O 2 levels in roadside Urginea maritima leaves when compared with those growing at the control site.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 91%
“…Agbaire & Akporhonor (2014) reported that tolerant plant species have the capacity to maintain high RWC under pollution stress, while less resistant species showed a decrease in their RWC. Hydrogen peroxide (H 2 O 2 ) is a reactive oxygen species that is produced in plant cells under normal conditions, but increased levels indicate oxidative stress (Khairallah et al 2018). Proline and carotenoids are stress-associated molecules that scavenge harmful ROS and protect plants from oxidative damage (Khairallah et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of variance shows the changes in the average quantitative variables with respect to the levels of categorical variables, as illustrated in several studies [44][45][46][47]. This study is significant since it promotes the use of cost-effective and eco-friendly use of passive bio-indicators to complement the physico-chemical approaches for air quality valuation [11,12,48], in line with the United Nations Sustainable Development Goals (SDGs) 3, 7, 11, and 13 for the substantial reduction of air pollution. This is apt, especially in environments devoid of air quality monitoring stations such as in the current study [49].…”
Section: Introductionmentioning
confidence: 94%
“…A number of previous studies have also shown a similar correlation between APTI and other biochemical parameters. [69][70][71][72] P = Polluted site, C = Control site Fig. -9: A Box and Whisker Plot for Sampling Session.…”
Section: Box and Wisker Plotmentioning
confidence: 99%